DI-091 Assessment of an education program for patients treated with oral anticoagulants in a cardiology department: a pilot study. (24th March 2015) - Eychenne, N; Brito, E; De Terline, D; Profizi, E; Roudot, M; Hue, B; Fernandez, C; Ederhy, S; Cohen, A; Antignac, M
Abstract : Background: In January 2013, an education program for patients treated with oral anticoagulants called " ETAP " was implemented in the cardiology department of our hospital. The day after the educational intervention, patient knowledge and coping are assessed but long-term knowledge, coping and medicines adherence have never been investigated up to now. Purpose: To assess long-term knowledge, coping and adherence of patients enrolled in ETAP since January 2013. Material and methods: 1) January 2013–August 2014 : During hospitalisation, an initial "knowledge and coping score" (E1 score: 0 to 10 points) was awarded for patients enrolled in the education program with a specific questionnaire designed by the ETAP team. 2) June–September 2014 : At least one month after discharge from the hospital, a pharmacy student called every patient at home who had given his verbal consent beforehand. A long-term "knowledge and coping score" (E2 score) was awarded with the same questionnaire. Medicines adherence was calculated with the 8-item Morisky Medication Adherence Scale (MMAS-8). Results: Of the 236 patients contacted, 100 patients completed the study. Mean "knowledge and coping scores" were both above 8 points (E1: 8.61 ± 2.36, E2: 8.23 ± 2.03). No significant difference (p = 0.35) was observed between means of E1 and E2 scores. MMAS-8 showed that most patients (70%) had a high level of adherence. No correlation was observed between E1 or E2 scores and adherence. Conclusion: The results of this pilot study suggest that most patients retain their long-term knowledge and coping skills. These data are in agreement with other studies. 1 The medicines adherence to oral anticoagulants estimated by MMAS-8 was higher than in routine practice. Assessment of the ETAP program should be improved by including biological and clinical outcomes such as INR or bleeding events collection. Reference: Thiriat N, et al . Therapeutic education of elderly patients under antivitamin - K treatment: evaluation of the program after 5 years. J Pharm Belg 2014;(3):30–7 No conflict of interest.